THE SYNTACTIC ANALYSIS OF THE COMPOUND SENTENCE IN THE JOURNALISTIC SUB-STYLE OF THE STANDARD MACEDONIAN LANGUAGE (Philological Studies, 2019)
The compound sentences that contain three or more predicative entities, i.e. part-sentences (independent or dependent) and are a part of the journalistic substyle in the Macedonian standard language are a real challenge regarding their syntactic analysis for the Macedonian language researches. Therefore, the aim of the paper is to present that the syntactic analysis of these sentences shows many dilemmas and that regarding the Minova-Gjurkova’s Syntax cannot be fully valid. In the same time, the paper shows that in the syntactic analysis of these sentences the reconstruction and the nominalization have a very important role.
Keywords: compound sentence, syntactic analysis